Área de Libre Comercio para las Américas: ¿emulación integracionista y construcción de actores? - Iguíñiz Echeverría, Javier (Economia, 2004)
Several producers' associations and groups of civil society in Latin America are involvedin campaigning against the signature of some components or of the whole FreeTrade Area of the Americas (FTAA). In this analysis of the agents and strategies involvedwe sustain that the participation in the negotiations is a necessary condition for thematuring of a South American alternative to the FTAA. Both, adors and strategies arebuilt or strengthened in the process of negotiation.